2022
DOI: 10.3390/fluids7120365
|View full text |Cite
|
Sign up to set email alerts
|

Bubble Growth in Supersaturated Liquids

Abstract: Bubble formation and dissolution have a wide range of industrial applications, from the production of beverages to foam manufacturing processes. The rate at which the bubble expands or contracts has a significant effect on these processes. In the current work, the hydrodynamics of an isolated bubble expanding due to mass transfer in a pool of supersaturated gas–liquid solution is investigated. The complete scalar transportation equation (advection–diffusion) is solved numerically. It is observed that the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…This observation suggests that the photolysis reaction in concentrated solution can produce enough N 2 molecules to transiently overcome the saturation limit in CHCl 3 and nucleate bubbles. 38 Without light exposure, however, these bubbles quickly dissipate as the N 2 molecules dissolve into the surrounding liquid, and the local concentration falls below the saturation limit. In order to create bubbles that persist after removal of light, they must be stabilized somehow.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This observation suggests that the photolysis reaction in concentrated solution can produce enough N 2 molecules to transiently overcome the saturation limit in CHCl 3 and nucleate bubbles. 38 Without light exposure, however, these bubbles quickly dissipate as the N 2 molecules dissolve into the surrounding liquid, and the local concentration falls below the saturation limit. In order to create bubbles that persist after removal of light, they must be stabilized somehow.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Under the experimental conditions of Triplett, the phenomenon of stratified flow, which often occurs in the macro field of gas-liquid two-phase flow, has not been observed. In stratified flow, gas-liquid two-phase flows up and down the pipe respectively, with obvious phase boundaries in the middle, and stratified flow cannot produce bubbles [8]. Chung et al showed that slug flow, mixed flow and slug annular flow accounted for a large proportion in the flow pattern diagram, indicating that these three flow patterns were more likely to occur under the conditions of gas-liquid flow rate shown in the diagram [9].…”
Section: Introductionmentioning
confidence: 99%
“…During the foaming process, the gas bubbles are generated, grow in size, and then stabilize during the acid-catalyzed curing reaction of the phenolic resins. 4 Bubble nuclei result from the mixing of foaming agents with the polymeric resin. The bubble growth is affected by several factors including the amount and nature of foam constituents, molding process, equipment, melt viscosity, gas permeability, foaming agents, temperature, and pressure.…”
Section: Introductionmentioning
confidence: 99%
“…Gas bubbles can also be due to the vaporization of blowing agents with lower boiling points. During the foaming process, the gas bubbles are generated, grow in size, and then stabilize during the acid‐catalyzed curing reaction of the phenolic resins 4 . Bubble nuclei result from the mixing of foaming agents with the polymeric resin.…”
Section: Introductionmentioning
confidence: 99%